Effects of High-Intensity Interval Training and Moderate-Intensity Training on Stress, Depression, Anxiety, and Resilience in Healthy Adults During Coronavirus Disease 2019 Confinement: A Randomized Controlled Trial - Borrega-Mouquinho, Yolanda; Sánchez-Gómez, Jesús; Fuentes-García, Juan Pedro; Collado-Mateo, Daniel; Villafaina, Santos (Frontiers in Psychology, 2021)
Objective: To compare the effects of two intervention programs: 1) High-intensity interval training (HIIT); and 2) Moderate intensity training (MIT), on anxiety, depression, stress and resilience during confinement caused by the COVID-19 in healthy adults. Methods: A total of 67 adults participated were randomly assigned to two groups: HIIT and MIT groups. The MIT group had to perform a home-based intervention based on aerobic exercises, whereas the HIIT group had to perform a home-based intervention based on HIIT exercises. The two groups (HIIT and MIT) had to complete the same physical exercise volume, 40 min per session (6 days per week) during the confinement period (6 weeks). Depression, anxiety, stress and resilience were assessed before and after the intervention. Results: Results showed that HIIT and MIT significantly reduced the stress, anxiety, depression as well as increase the resilience (p-value<0.05). Moreover, the improvements obtained in the HIIT group seem to be greater than those of the MIT group in depression (p-value<0.05). Conclusions: HIIT and MIT decreased anxiety, stress, depression as well as increased resilience during the COVID-19 confinement. In addition, the HIIT intervention seemed to be more beneficial to reduce depression than the MIT intervention.